Recent progress in the improvement of hydrothermal stability of zeolites. Issue 22 (17th May 2021) - Simancas, Raquel; Chokkalingam, Anand; Elangovan, Shanmugam P.; Liu, Zhendong; Sano, Tsuneji; Iyoki, Kenta; Wakihara, Toru; Okubo, Tatsuya
Abstract : This review attempts to summarize the recently developed strategies to improve the hydrothermal framework stability of zeolites. Abstract : Zeolites have been successfully employed in many catalytic reactions of industrial relevance. The severe conditions required in some processes, where high temperatures are frequently combined with the presence of steam, highlight the need of considering the evolution of the catalyst structure during the reaction. This review attempts to summarize the recently developed strategies to improve the hydrothermal framework stability of zeolites.